2015
DOI: 10.1093/jncimonographs/lgv014
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric and Multimodality Functional Radiological Imaging for Breast Cancer Diagnosis and Early Treatment Response Assessment

Abstract: Breast cancer is the second leading cause of cancer death among US women, and the chance of a woman developing breast cancer sometime during her lifetime is one in eight. Early detection and diagnosis to allow appropriate locoregional and systemic treatment are key to improve the odds of surviving its diagnosis. Emerging data also suggest that different breast cancer subtypes (phenotypes) may respond differently to available adjuvant therapies. There is a growing understanding that not all patients benefit equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…26 The integration of multiple imaging modalities results in the combination of different functional imaging metrics, allowing for enhanced characterization of tumor physiology and microenvironment, before and after treatment. 26,97 Beginning with the development of hybrid PET/CT and SPECT/CT scanners, early multimodality imaging technologies aimed to pair molecular imaging data with high-resolution anatomical data for improved lesion localization and detection. 26,97 Studies evaluating 18 F-FDG-PET prediction of breast cancer NAT response predominantly use PET/CT scanners to image radiotracer uptake, and demonstrate improved lesion detection over CT evaluation alone.…”
Section: Emerging Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The integration of multiple imaging modalities results in the combination of different functional imaging metrics, allowing for enhanced characterization of tumor physiology and microenvironment, before and after treatment. 26,97 Beginning with the development of hybrid PET/CT and SPECT/CT scanners, early multimodality imaging technologies aimed to pair molecular imaging data with high-resolution anatomical data for improved lesion localization and detection. 26,97 Studies evaluating 18 F-FDG-PET prediction of breast cancer NAT response predominantly use PET/CT scanners to image radiotracer uptake, and demonstrate improved lesion detection over CT evaluation alone.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…26,97 Beginning with the development of hybrid PET/CT and SPECT/CT scanners, early multimodality imaging technologies aimed to pair molecular imaging data with high-resolution anatomical data for improved lesion localization and detection. 26,97 Studies evaluating 18 F-FDG-PET prediction of breast cancer NAT response predominantly use PET/CT scanners to image radiotracer uptake, and demonstrate improved lesion detection over CT evaluation alone. 87,98 More recently, there has been interest in pairing PET with MRI, to determine if the additional anatomical and functional characterizations derived from MRI can improve prediction of NAT response in breast cancer patients.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…Moreover, the MRI parameters, as well as, the time resolution of the DCE image phases used to train the MPDL model were different for our dataset and the validation dataset reasserting the robust nature of the MPDL model and eliminates the need to "retrain" the MPDL model. The mpMRI parameters used in this study were based on our and others previous results in patients 1,3,4,30 . These studies demonstrated that the combined MRI sequences consisting of DWI, ADC, and PK-DCE were highly correlated with the histological phenotype of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Combined imaging modalities frequently use contrast agents-radiopharmaceuticals, intravascular agents, and multifunctional nanoparticles to expand their capabilities. 27,28 Since conventional CT and MRI currently use different dedicated agents, [29][30][31][32] the potential for multifunctional CT-MRI nanoparticles is particularly important. 33…”
Section: B Simultaneous Ct-mrimentioning
confidence: 99%